2010
DOI: 10.1089/hyb.2009.0118
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies to Ki-67 Protein Suitable for Immunohistochemical Analysis

Abstract: Detection of cell proliferation index is widely used in experimental and clinical research. Earlier it was shown that nuclear Ki-67 protein expression is strictly related to cell proliferation. It was revealed during all active phases of the cell cycle in mammals but was absent in G0 phase, so Ki-67 presence in cell nuclei reflects a potential growth fraction of whole cell population. The main area of Ki-67 antibody application is in immunocytochemical and immunohistochemical analyses. The aim of our work was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…2). Immunofl uorescent analysis was performed as described [50]. Our fi ndings support a hypothesis that mTOR phosphorilated at Ser 2481 interacts with microtubules during cytokinesis.…”
Section: The Crosstalk Between Mtor Kinase and Microtubulessupporting
confidence: 74%
“…2). Immunofl uorescent analysis was performed as described [50]. Our fi ndings support a hypothesis that mTOR phosphorilated at Ser 2481 interacts with microtubules during cytokinesis.…”
Section: The Crosstalk Between Mtor Kinase and Microtubulessupporting
confidence: 74%
“…In addition we found Major components of the PI3K/mTOR/S6K signalling pathway correlation between nuclear accumulation of S6K2 (but not S6K1) and Ki67 and PCNA expression that indicates involvement of S6K2 in malignant cells growth regulation [22]. In support to this observation using in vitro 3D primary monolayer cell culture of thyrocytes, obtained from undamaged follicles, we demonstrated that down regulation of thyrocyte functional activity (dedifferentiation) caused by the loss of follicle organization was accompanied by subcellular redistribution (increase in nuclear content) of S6K1 and S6K2 [24][25][26].…”
supporting
confidence: 68%
“…Afterwords mouse monoclonal antibodies against Ki-67 protein (1:200) were added to the cells and incubated overnight at 4 °C. The anti-Ki-67 antibodies were generated and evaluated earlier [37]. The TRITC-AffiniPure Goat Anti-Mouse IgG (H+L) secondary antibody (Jackson ImmunoResearch Labs, USA) was applied at 1:400 for 40 min at 37 °C in humidified chamber.…”
Section: Fluorescence and Confocal Laser Scanning Microscopymentioning
confidence: 99%